2009
DOI: 10.1016/j.ydbio.2009.05.538
|View full text |Cite
|
Sign up to set email alerts
|

A conserved Six–Eya cassette acts downstream of Wnt signaling to direct non-myogenic versus myogenic fates in the C. elegans postembryonic mesoderm

Abstract: The subdivision of mesodermal cells into muscle and non-muscle cells is crucial to animal development. In the C. elegans postembryonic mesoderm, this subdivision is a result of an asymmetric cell division that leads to the formation of striated body wall muscles and non-muscle coelomocytes. Here we report that the Six homeodomain protein CEH-34 and its cofactor Eyes Absent, EYA-1, function synergistically to promote the non-muscle fate in cells also competent to form muscles. We further show that the asymmetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(62 citation statements)
references
References 68 publications
2
56
0
Order By: Relevance
“…3 D and E). A similar expression pattern for a ceh-34::gfp transgene has been independently observed (22). We observed that our ceh-34::gfp transgene was expressed in all pharyngeal neurons (M4, I1, MI, I3, M3, NSM, MC, I2, I4, I5, I6, M1, M2, and M5), some pharyngeal muscle cells (pm1 and pm2) and pharyngeal epithelial cells (e1 and e3), and some body wall muscles around the anterior pharynx (Fig.…”
Section: Ceh-34 Is Expressed Predominantly In the Nuclei Of Pharyngeasupporting
confidence: 73%
See 1 more Smart Citation
“…3 D and E). A similar expression pattern for a ceh-34::gfp transgene has been independently observed (22). We observed that our ceh-34::gfp transgene was expressed in all pharyngeal neurons (M4, I1, MI, I3, M3, NSM, MC, I2, I4, I5, I6, M1, M2, and M5), some pharyngeal muscle cells (pm1 and pm2) and pharyngeal epithelial cells (e1 and e3), and some body wall muscles around the anterior pharynx (Fig.…”
Section: Ceh-34 Is Expressed Predominantly In the Nuclei Of Pharyngeasupporting
confidence: 73%
“…4B). CEH-34 and EYA-1 also have been shown by others to both act to specify coelomocyte cell fate and interact physically (22).…”
Section: Eya-1 Forms An Evolutionarily Conserved Complex With the Sixmentioning
confidence: 82%
“…sem-2(RNAi) construct pCXT9 was made by subcloning the sem-2 cDNA fragment from yk657g12 into L4440 (Timmons and Fire, 1998). pNMA49 and pNMA50 were used for knocking down fozi-1 and mab-5, respectively (Amin et al, 2009).…”
Section: Plasmid Constructs and Transgenic Linesmentioning
confidence: 99%
“…Transgenic lines were generated using the plasmids pRF4 (Mello et al, 1991), pJKL449 (myo-2p::gfp::unc-54 3Ј UTR) (Jiang et al, 2009) or LiuFD61 (mec-7p::mRFP) (Amin et al, 2009) as markers.…”
Section: Plasmid Constructs and Transgenic Linesmentioning
confidence: 99%
See 1 more Smart Citation